2019
DOI: 10.1590/1414-431x20198533
|View full text |Cite
|
Sign up to set email alerts
|

A newly designed intensive caregiver education program reduces cognitive impairment, anxiety, and depression in patients with acute ischemic stroke

Abstract: This study aimed to evaluate the effect of a newly designed intensive caregiver education program (ICEP) on reducing cognitive impairment, anxiety, and depression in acute ischemic stroke (AIS) patients. One hundred and ninety-six AIS patients were divided into ICEP group and Control group in a 1:1 ratio using blocked randomization method. In the ICEP group, the caregivers received ICEP, while in the Control group caregivers received usual education and guidance. All patients received conventional rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 31 publications
2
65
0
10
Order By: Relevance
“…Although this observation needs to be confirmed in larger studies, these data support the usefulness of an early clinical awareness regarding emotional symptoms in TIA patients. Standardized aftercare concepts -as already tested in stroke patients [37,38] -including for instance rehabilitative aspects, caregiver education, and psychometric assessment could in this context also represent useful tools for TIA patients [39]. An early identification of patients at risk would allow interventions such as supporting information, pharmacological and non-pharmacological treatments with the intention to prevent long-term non-physical TIA sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Although this observation needs to be confirmed in larger studies, these data support the usefulness of an early clinical awareness regarding emotional symptoms in TIA patients. Standardized aftercare concepts -as already tested in stroke patients [37,38] -including for instance rehabilitative aspects, caregiver education, and psychometric assessment could in this context also represent useful tools for TIA patients [39]. An early identification of patients at risk would allow interventions such as supporting information, pharmacological and non-pharmacological treatments with the intention to prevent long-term non-physical TIA sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Self-rating anxiety scale (SAS), self-rating depression scale (SDS), and MoCA were usually used for cognitive function estimation [17]. Both on the beginning day of therapy and the completion of therapy (after 14 days), the SAS, SDS, and MoCA were used to assess cognitive function in all groups.…”
Section: Population and Methodsmentioning
confidence: 99%
“…The importance of training and education for caregivers is also supported by other studies that showed a reduction in complications through providing education programs to caregivers. 12 This role can be seen in the following quotes:…”
Section: Roles Of Caregiver: Communicationmentioning
confidence: 99%